Melodi Ejaan Bahasa Arab: Kajian Kesalahan Fonologi dalam Qiroatur Rosyidah Siswa SMP - Lintang Lutfhi Kirani; Rima Alfiatul Azizah; Lisma Meilia Wijayanti (CV Edujavare Publishing, 2024)
The research aims to determine the form and factors causing phonological errors in reading Qiroatur Rosyidah class VIII at SMP Muhammadiyah 1 Ponorogo. The method used is a descriptive qualitative method with interview and documentation data collection techniques. The results of the research are the forms of phonological errors that occur in the Qiro'atur Rosyidah reading of class VIII students at SMP Muhammadiyah 1 Ponorogo, namely shifts in the meaning of letters, errors in pronouncing harakat and the students' lack of attention to the length and shortness of a sentence. This phonological error factor occurs due to reading speed, students' lack of concentration when reading and physical factors, namely a nasal voice. The solution to this phonological error is warnings regarding students' reading speed, strengthening letter makhorijul, and reading talaqqi from the subject teacher.